The multilateral trade regime: A global public good for all? - Mendoza, Ronald U (Archīum Ateneo, 2003)
The structure of arrangements for multilateral trade has caused much controversy, as was witnessed by the WTO ministerial conference at Seattle in 1999 and on other occasions. Examines the problem through the lens of the global public goods concept. It suggests that to become a global public good in substance rather than merely in form, the multilateral trade regime requires adjustments to correct a distributional imbalance favouring developed countries at the expense of developing countries.